Building citizenship through language and internacionalization - Finardi, Kyria Rebeca; Furtado Guimarães, Felipe (Guará Journal, 2018)
This study aims to describe a project related to university services entitled “Building citizenship through language”, whose objective was to promote the development of global citizenship of the target academic community, through activities connected to the use of foreign languages in general and of English in particular. An additional objective of the project was to promote the internationalization of the higher education institution where the project was developed. The research methodology is qualitative and descriptive and the results of the analysis of the project suggest that it had a key role in the development of internationalization in the institution studied. The study concludes that university services integrated to the institutional planning are important to promote and support the development of the process of institutional internationalization.